Pelatihan dan Pengembangan Manajemen Limbah Organik Ketela sebagai Diversifikasi Produk Layak Hilirisasi Industri Tape Desa Banjarsari - Hidayat, Rachmad; Suharsono, Naswan; Hari, Mohammad; Salsabila, Annisa Ayu; Surya, Eka Putri; Ningrum, Linda Agustin; Aruna, Alby; Marcelliantika, Adinda (IAI Nasional Laa Roiba Bogor, 2024)
Training and development in organic cassava waste management is a strategic step towards product diversification and downstreaming of the tape industry in Banjarsari Village. This program aims to increase the added value of organic cassava waste through environmentally friendly and marketable product innovations. The methods used include practical training, technical assistance, and business sustainability evaluation. The results of this activity indicate an improvement in the community's skills and knowledge in managing cassava waste, as well as the creation of diversified products with potential for further development. Thus, this program is expected to support the sustainability of the tape industry in Banjarsari Village while enhancing the welfare of the local community.